Outcomes of Patients With Long-Term Treatment Response to Vascular Endothelial Growth Factor-Targeted Therapy for Metastatic Renal Cell Cancer - Buchler, Tomas; Poprach, Alexandr; Bortlicek, Zbynek; Lakomy, Radek; Chloupková, Renata; Vyzula, Rostislav; Zemanova, Milada; Kopeckova, Katerina; Svoboda, Marek; Slaby, Ondrej; Kiss, Igor; Studentova, Hana; et al. (Clinical genitourinary cancer, 2017)
BACKGROUND: Although targeted therapies with inhibitors of the vascular endothelial growth factor (VEGF) are the mainstay of treatment for metastatic renal cell carcinoma, there are limited data on the outcome of patients with long-term response to this treatment. PATIENTS AND METHODS: In a retrospective, registry-based study, patients continuously treated with first-line anti-VEGF agents for at least 24 months were included. In total, 219 patients had evaluable data and were included in the outcome analysis. RESULTS: Median progression-free survival (PFS) after initiation of first-line targeted therapy was 39.7 months (95% confidence interval [CI], 35.9-43.5 months), with 5-year PFS of 34.2% (95% CI, 27.2%-41.2%). Median overall survival (OS) reached 79.1 months (95% CI, 65.2-93.0 months) with the 5-year OS of 62.1% (95% CI, 54.5%-69.7%). In this cohort, 28, 103, and 88 patients achieved complete response (CR), partial response (PR), or stable disease (SD) as the best response, respectively. Median PFS and OS were comparable in patients with PR and SD, but significantly longer in patients with CR (log rank test P value for PFS difference < .001 and .009 for OS difference). CONCLUSION: There are marked differences in PFS and OS between patients who receive long-term anti-VEGF treatment, achieving CR and non-CR as the best clinical response. Patients with non-CR experienced a relatively high progression rate shortly after the landmark time point of 2 years.
Keywords: Molecular Targeted Therapy; senioři; indazoly; metastázy nádorů; analýza přežití; Phenylurea Compounds; Angiogenesis Inhibitors; Sorafenib; Survival; Carcinoma, Renal Cell; Indoles; Sunitinib; senioři nad 80 let; vaskulární endoteliální růstový faktor A; Niacinamide; Retrospective Studies; Survival Analysis; lidé; niacinamid; výsledek terapie; pyrroly; Middle Aged; registrace; mužské pohlaví; Indazoles; sorafenib; karcinom z renálních buněk; Adult; Renal cell carcinoma; Pyrimidines; sulfonamidy; bevacizumab; pyrimidiny; sunitinib; Kidney Neoplasms; Registries; Bevacizumab; Pyrroles; Aged, 80 and over; Pazopanib; Neoplasm Metastasis; Disease-Free Survival; ženské pohlaví; Sulfonamides; retrospektivní studie; Humans; lidé středního věku; Vascular Endothelial Growth Factor A; indoly; cílená molekulární terapie; dospělí; inhibitory angiogeneze; Female; Aged; Treatment Outcome; přežití bez známek nemoci; nádory ledvin; Male; fenylmočovinové sloučeniny